Deciphering the complexity of enteric niches in Hirschsprung disease: from metaphorical insights to therapeutic transformation - Yu, Hui; Pan, Weikang; Tian, Donghao; Gao, Ya (Frontiers in Pediatrics, 2025)
Hirschsprung disease (HSCR) is a congenital disorder marked by the absence of ganglion cells in the distal bowel, resulting in severe constipation and bowel obstruction. Surgery is currently the primary treatment for HSCR. However, post-surgical outcomes are unsatisfactory, merely alleviating symptoms of intestinal obstruction. Up to one-third of HSCR patients continue to experience gastrointestinal issues post-surgery, which severely impacts their growth and development and may even threaten their lives. Cell transplantation represents a promising strategy for the radical treatment of HSCR but faces numerous challenges. The mismatch between transplanted cells and the enteric niches is one of the key obstacles in reconstructing the enteric nervous system through cell transplantation. There is an urgent need to “get to the root of the problem” to enhance our understanding of the enteric niches and overcome current limitations. This review synthesizes insights from two metaphorical narratives, “Blind Men and the Elephant” and “Rags To Riches,” to provide a comprehensive re-understanding of the enteric niches and their potential for enteric neurogenesis. By examining these narratives, we underscore the importance of the enteric niches in the potential for transformative discoveries in HSCR research.